Land Use Under Homestead in Kerala: The Status of Homestead Cultivation from a Village Study - Sr. Sheeba Andrews Elumalai Kannan (The Institute for Social and Economic Change, 2016)
This paper is an attempt to analyse the land use under homestead in the context of land-use change that has been extensively taking place in Kerala. The features of homestead gardening, its importance, the present status and the obstacles in home gardening have been given prime focus. Homesteads are traditionally used for self-sufficiency and pleasure. But due to real estate boom, we observe large scale conversion of agricultural land and fragmentation of holdings. In this context, homestead cultivation is considered to be the most suitable form of cultivation. The study finds underutilisation of land under homesteads due to lack of sufficient incentives for growing in homestead. Though the structural and functional diversity of the traditional homestead gardening has been not observed, a preference for perennial crops makes the homestead more homogeneous across households. Such monoculture affects not only food security but also biodiversity and ecology. This situation may lead to a disappearance of home gardens in Kerala